EFEKTIVITAS PENGGUNAAN MEDIA ALAT PERAGA KONKRET TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA KELAS III DI SD NEGERI 95 PALEMBANG - Imam Wijaya; Andi Rahman; Mutiara Fajar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effectiveness of using concrete teaching aids on students' learning outcomes in Mathematics, particularly on multiplication material, for Grade III students at SD Negeri 95 Palembang, specifically Class III.A. The research employed a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The study applied a saturated sampling technique, involving 18 students from Class III.A as the research sample. Data analysis techniques included the normality test, homogeneity test, and hypothesis testing using the paired sample t-test.The results of the hypothesis test showed that the Sig. (2-tailed) value was 0.001 < 0.05 and the calculated t-value was greater than the t-table value, indicating that H₀ was rejected and Hₐ was accepted. Therefore, it can be concluded that the use of concrete teaching aids is effective in improving students' learning outcomes in mathematics learning for Grade III students at SD Negeri 95 Palembang. The improvement in students' learning outcomes was also reflected in the increase of the average pretest score from 47.78 to 81.11 in the posttest, with an N-Gain score of 0.64 (64%), which falls into the moderate or fairly effective category